Postnatal Ovary Development in the Rat: Morphologic Study and Correlation of Morphology to Neuroendocrine Parameters. (April 2015) - Picut, Catherine A.; Dixon, Darlene; Simons, Michelle L.; Stump, Donald G.; Parker, George A.; Remick, Amera K.
Histopathologic examination of the immature ovary is a required end point on juvenile toxicity studies and female pubertal and thyroid function assays. To aid in this evaluation and interpretation of the immature ovary, the characteristic histologic features of rat ovary through the developmental periods are described. These histologic features are correlated with published changes in neuroendocrine profiles as the hypothalamic–pituitary–gonadal axis matures. During the neonatal stage (postnatal day [PND] 0–7), ovarian follicle development is independent of pituitary gonadotropins (luteinizing hormone [LH] or follicle-stimulating hormone [FSH]), and follicles remain preantral. Antral development of "atypical" follicles occurs in the early infantile period (PND 8–14) when the ovary becomes responsive to pituitary gonadotropins. In the late infantile period (PND 15–20), the zona pellucida appears, the hilus forms, and antral follicles mature by losing their "atypical" appearance. The juvenile stage (PND 21–32) is the stage when atresia of medullary follicles occurs corresponding to a nadir in FSH levels. In the peripubertal period (PND 33–37), atresia subsides as FSH levels rebound, and LH begins its bimodal surge pattern leading to ovulation. This report will provide pathologists with baseline morphologic and endocrinologic information to aid in identification and interpretation of xenobiotic effects in the ovary of the prepubertal rat.